THE IMPACT OF SHARE OFFERING VOLUME FACTOR ON SYSTEMATIC RISK: APPLICATION OF THE COMMON EFFECT PANEL DATA REGRESSION METHOD (STUDY ON JII STOCKS IN THE INDONESIA STOCK EXCHANGE JANUARY - APRIL 2020 PERIOD) STUDY OF THE COVID-19 VIRUS PANDEMIC - Marina Malian (Laboratorium Riset Ekonomi, 2022)
This study aims to determine the impact of Stock Offer Volume on Systematic Risk. This study uses the object of stocks in the JII (Jakarta Islamic Index) group which is listed on the Indonesia Stock Exchange (BEI) for the period January to April 2020 with a saturated sample (census sampling) as a method. There are 20 stocks selected as samples. The method of analysis of this research is panel data regression with the common effect method. The study found that the results of the volume of stock offerings have a positive and significant effect on systematic risk.